STUDI TENTANG BENTUK DAN PENEMPATAN MOTIF UKIRAN PADA RUMAH GADANG ALANG BABEGA DAN RUMAH GADANG DT. RAJO BAGINDO MALANO DI BATUSANGKAR - RAMENDRA YUZA, Drs. Efrizal, M.Pd., Drs. Syafwan, M.Si. (Universitas Negeri Padang, 2016)
This study aims to: Describe 1) forms the motif carving 2) placement of the motif carving 3) the shape and placement of the motif carving in the rumah gadang Alang Babega and Dt. Rajo Bagindo Malano. The research method using qualitative research with descriptive approach. The results showed that the shape of the motif carving on the both namely the form of plants, animals and geometric. Placement motif carving on the papan banyak, singok and dinding hari. The shape and placement of the motif carving on both the Rumah Gadang is different, only some a few motif carving are same.Keywords: Form, placement, comparation